Method for preparing ceramic-based composite material through rapid reactive infiltration and application of ceramic-based composite material
通过在陶瓷基复合材料制备中采用焦耳加热设备进行快速反应熔渗,解决了传统方法中制备时间长、能耗高和抗烧蚀性能差的问题,实现了高效、低能耗的陶瓷基复合材料制备,提升了材料的力学和抗氧化烧蚀性能。
Patent Information
- Application Number
- CN202510176382.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-04-25
AI Technical Summary
The traditional reaction seepage method has a long time to contact the melt with the C/C matrix during heating and long contact with the melt, resulting in low preparation efficiency, high energy consumption, uneven composition and degraded ablation performance.
The Joule heating equipment is used to perform rapid reaction and permeation. Through ultra-high heating rate and fast cooling rate, the preparation time is shortened to 1-2 hours, reduce energy consumption, and improve the composition uniformity and oxidation and ablation resistance of ceramic matrix composite materials.
It significantly improves the preparation efficiency of ceramic matrix composite materials, reduces energy consumption, and prepares materials with low porosity, uniform composition and good interface bonding, which improves its mechanical properties and oxidation and ablation resistance.
Smart Images

Figure CN119874398A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a ceramic-based composite material by rapid reaction infiltration and application thereof, belonging to the field of preparation of ceramic-based composite materials. Background Art
[0002] With the development of ultra-high-speed and atmospheric round-trip aircraft, the disadvantages of traditional metal materials such as high density, low melting point and poor oxidation resistance have begun to emerge, making it difficult to meet the harsh operating conditions of aircraft. High-performance materials with lighter weight, higher strength and oxidation resistance are needed to replace them. C / C composites, namely carbon fiber reinforced carbon-based composites, have the advantages of low density, high specific strength, small thermal expansion coefficient, good ablation resistance and thermal shock resistance. Their high-temperature performance is far superior to traditional metal-based materials and is widely used in thermal structural components of various aerospace aircraft. It is particularly worth mentioning that C / C composites are the only type of materials whose mechanical properties increase instead of decrease at 2000°C. However, C / C composites will oxidize above 350°C, causing material failure, which seriously hinders their application in aerospace and other fields. Many studies have shown that adding ceramic phases to C / C composites to prepare ceramic-based composites can effectively improve their oxidation resistance and ablation resistance.
[0003] In the early stage of research, SiC ceramics were added to improve the ablation resistance, but SiC's oxidation product SiO2 has a low melting point (1723°C), boiling point (2230°C), high vapor pressure and active oxidation characteristics, which limits its application in temperatures above 1650°C. Ultra-high temperature ceramics (UHTC) have a melting point above 3000°C and high strength. They are considered to be an important material for improving the application of C / C composites under ultra-high temperature conditions and are favored by many researchers.
[0004] However, UHTC forms a porous structure after oxidation at low and medium temperatures, and the thermal expansion coefficients of the oxidation products and C / C composites are quite different, which can easily cause the oxide layer to crack and form oxygen diffusion channels, resulting in a decrease in anti-ablation performance. Therefore, researchers combined SiC with UHTC and used the low melting point of SiC oxidation product SiO2 to fill the defects formed after UHTC oxidation, which is an effective method to improve the anti-ablation performance of C / C composites.
[0005] Currently, there are many methods for preparing ceramic matrix composites, including chemical vapor infiltration (CVI), precursor infiltration and pyrolysis (PIP), slurry infiltration (SI), reactive melt infiltration (RMI), etc. These processes mainly involve the infiltration and deposition of reactive gases, the infiltration and in-situ reaction of alloy melts, the impregnation and pyrolysis of liquid precursors, and the pre-impregnation of ceramic slurries. Among them, reactive melt infiltration is widely used in the preparation of ceramic matrix composites because of its advantages of low manufacturing cost, high utilization rate of infiltration materials, and easy realization of near-net shape.
[0006] The reaction infiltration method refers to the use of metal powder or block to embed and cover the porous C / C preform, which is then placed in a vacuum condition or a slightly positive pressure atmosphere. The metal is melted by heating. The molten metal will penetrate into the porous carbon matrix under the action of capillary force and react rapidly with the matrix carbon to form a ceramic phase, thereby preparing a ceramic-based composite material. At present, researchers have introduced SiC ceramics and / or ultra-high temperature ceramics (such as HfC, ZrC) into C / C composites through reaction infiltration technology to prepare a variety of ceramic-based composite materials. However, the reaction infiltration method usually uses a vacuum carbon tube furnace for heating, which has the disadvantages of long heating cycle, low thermal efficiency, and high energy consumption. In addition, for the reaction infiltration of some refractory metals, it is often necessary to heat to above 2000°C. If used for a long time, very stringent requirements are placed on the heating furnace. In particular, the traditional reaction infiltration method often takes more than 12 to 24 hours. The long high-temperature treatment process will also lead to the graphitization transformation of the C / C matrix, causing the debonding of the carbon fiber and the matrix carbon. At the same time, it will also cause the metal melt to directly corrode the carbon fiber, damaging its mechanical properties and thermal shock resistance.
[0007] Therefore, if the heating process of the reaction infiltration method can be accelerated, the heating time of the C / C matrix and the contact time between the melt and the C / C matrix can be greatly reduced, the above problems are expected to be solved. However, so far, there are few reports on the use of Joule heat for rapid reaction infiltration to prepare ceramic matrix composites. Summary of the invention
[0008] In view of the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a method and application of preparing ceramic-based composite materials by rapid reaction infiltration. The method provided by the present invention adopts Joule heating equipment to carry out infiltration reaction, which changes the traditional heating method and shortens the time for preparing ceramic-based composite materials by reaction infiltration from more than 12-24 hours in the traditional method to within 1-2 hours. It not only greatly improves the preparation efficiency of the composite material but also reduces energy consumption. In addition, since the heating time is reduced, the contact time and probability of the high-temperature melt and the fiber are reduced, and a ceramic-based composite material with low porosity, uniform composition and good interface bonding can be prepared, which is also beneficial to improve its mechanical properties and anti-oxidation and ablation properties, and can be applied to high-temperature structural parts such as hypersonic aircraft nose cones, wing leading edges and engine nozzles.
[0009] In order to achieve the above-mentioned object, the present invention provides a method for preparing a ceramic-based composite material by rapid reaction infiltration, the method comprising: placing a C / C composite material body in a Joule heating device under vacuum or inert atmosphere and embedding / covering it with an infiltration raw material, rapidly heating it to the melting point of the infiltration raw material by Joule heating and keeping it warm for a certain period of time, so that the melt and the C / C body rapidly undergo infiltration reaction to generate a ceramic phase, thereby obtaining a ceramic-based composite material in a short time, and the rate of rapid heating is greater than or equal to 200°C / s.
[0010] In the present invention, the rapid heating rate is preferably greater than or equal to 200° C. / s, which of course includes 200-3000° C. / s.
[0011] In a preferred embodiment, the C / C composite material blank contains carbon fiber and carbon matrix, and its density is 0.5-1.8 g / cm 3 , the opening rate is 1%~80%.
[0012] In a more preferred embodiment, the density of the C / C composite body is 0.8-1.5 g / cm 3 , the opening rate is 10%-60%.
[0013] In a preferred embodiment, the ceramic-based composite material is composed of carbon fibers and a matrix, wherein the matrix is composed of ceramics and unreacted carbon.
[0014] In a preferred embodiment, the ceramic is a ceramic formed by the reaction of the infiltration raw material and the carbon matrix or a ceramic brought in from the raw material during infiltration, and the ceramic is a carbide or boride (including a multiphase mixture or solid solution) of metals and / or non-metals such as Si, Ti, Zr, Hf, Nb, Ta, rare earth, etc.
[0015] In a preferred embodiment, the infiltration raw materials are metal or non-metal elements, alloys and carbides, nitrides, borides, oxides of metal or non-metal elements such as Si, Ti, Zr, Hf, Nb, Ta, B, rare earth, and mixtures or solid solutions of the above raw materials.
[0016] In a more preferred embodiment, the infiltration raw material is selected from at least one of Si powder, Zr powder and Ti powder.
[0017] In a preferred embodiment, the infiltration raw material is in powder and / or block form, the particle size of the powder infiltration raw material is 10 nm-1 mm, and the size of the block infiltration raw material is ≥ (1×1×1) mm. 3 .
[0018] In a more preferred embodiment, the particle size of the powdered infiltration raw material is 0.5 μm to 75 μm.
[0019] It should be noted that the present invention has no special requirements on the mass ratio of the infiltration raw material and the C / C composite material blank, and any ratio known in the art can be used.
[0020] In a preferred embodiment, the C / C composite material blank is a cylinder with a diameter of 15-30 mm and a height of 5-10 mm.
[0021] In a preferred embodiment, the heating rate of the Joule heating device can reach 20,000°C / s, the maximum operating temperature is not less than 3,000°C, and the maximum cooling rate is not less than 1,000°C / min.
[0022] In a more preferred embodiment, the Joule heating insulation time is not less than 60 min, which can meet the insulation time requirement of the reactive infiltration process.
[0023] In a preferred embodiment, the conditions of the infiltration reaction are: heating to 1300°C~2100°C, preferably 1400°C~2000°C, more preferably 1550~2000°C, at a heating rate of 200~3000°C / s, preferably 500~3000°C / s, and further preferably 900~3000°C / s, keeping warm for 15~120min, preferably 15~60min, more preferably 20~60min, and further preferably 45~60min, and finally cooling to room temperature at a cooling rate of 100~1000°C / min, preferably 500~1000°C / min.
[0024] In a preferred embodiment, the inert atmosphere is nitrogen and / or argon.
[0025] In a more preferred embodiment, the pressure of the inert atmosphere is preferably -0.1 MPa to +0.1 MPa.
[0026] Compared with the prior art, the present invention has at least the following advantages:
[0027] (1) The method for preparing ceramic-based composite materials by rapid reaction infiltration provided by the present invention adopts Joule heating technology, has an ultra-high heating rate and a relatively fast cooling rate, and can shorten the time for preparing ceramic-based composite materials by reaction infiltration from more than 12-24 hours of the traditional method to within 1-2 hours, thereby greatly reducing the process cycle of reaction infiltration and realizing the rapid preparation of ceramic-based composite materials. Compared with traditional reaction infiltration, the present method has low equipment requirements, small heating current, and low power consumption, thus reducing energy consumption and cost and improving production safety.
[0028] (2) The preparation method provided by the present invention can quickly heat up to the melting point of all the infiltration raw materials, effectively avoiding the low powder utilization rate caused by the long heating process of the traditional reaction infiltration process, the low melting point powder preferentially entering the C / C matrix, and the fiber and matrix of the C / C composite material being in a high temperature state for a long time, thereby avoiding the problems of uneven composition, excessive erosion of carbon fiber by the melt, excessive graphitization of carbon fiber and pyrolytic carbon, and interface debonding caused by the above problems, which is beneficial to improving the mechanical properties and anti-oxidation and ablation properties of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a macroscopic morphology of the C / C-SiC-ZrC composite material obtained in Example 1 of the present invention;
[0030] Figure 2 The cross-sectional XRD and SEM images of the C / C-SiC-ZrC composite material obtained in Example 1 of the present invention; wherein: a-XRD image, b-SEM image;
[0031] Figure 3 This is a macroscopic morphology of the C / C-SiC-ZrC composite material obtained in Example 1 of the present invention after ablation;
[0032] Figure 4 The ablation surface temperature curve and XRD diagram of the C / C-SiC-ZrC composite material obtained in Example 1 of the present invention; wherein: a-temperature curve, b-XRD diagram;
[0033] Figure 5 This is the cross-sectional XRD pattern of the C / C-ZrC-SiC composite material obtained in Example 2 of the present invention;
[0034] Figure 6 This is a cross-sectional SEM image of the C / C-ZrC-SiC composite material obtained in Example 2 of the present invention;
[0035] Figure 7 This is the cross-sectional XRD pattern of the C / C-ZrC-SiC composite material obtained in Example 3 of the present invention;
[0036] Figure 8 This is the cross-sectional XRD pattern of the C / C-ZrC-TiC composite material obtained in Example 4 of the present invention;
[0037] Fig. 9 This is a macroscopic morphology of the C / C-SiC-ZrC composite material obtained in Comparative Example 1 of the present invention;
[0038] Fig.10 This is a cross-sectional SEM image of the C / C-SiC-ZrC composite material obtained in Comparative Example 1 of the present invention;
[0039] Fig.11 This is a macroscopic morphology of the C / C-SiC-ZrC composite material obtained in Comparative Example 1 of the present invention after ablation;
[0040] Fig.12 The ablation surface temperature curve and XRD diagram of the C / C-SiC-ZrC composite material obtained in Comparative Example 1 of the present invention; wherein: a-temperature curve, b-XRD diagram;
[0041] Fig.13 Schematic diagram of the Joule heating rapid reaction infiltration process of the present invention and the conventional reaction infiltration process and a comparison of the processing time; wherein: a-Joule heating, b-tube furnace heating. DETAILED DESCRIPTION
[0042] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0043] In the present invention, room temperature refers to 25±2°C.
[0044] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following specific embodiments. Obviously, the embodiments described below are only a part of the embodiments, and all other embodiments obtained by professionals in this field without creative work still belong to the protection scope of the present invention.
[0045] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0046] The density and porosity of the composite materials in the following examples are measured by conventional methods, and the ablation data are obtained in an air-plasma ablation environment.
[0047] The air-plasma ablation experiments described in the embodiments of the present invention are all carried out in accordance with the GJB 323B-2018 standard, and the specific experimental parameters are: argon flow rate of 2000L / h, hydrogen flow rate of 120L / h, power of 35kW, ablation distance of 60mm, inner diameter of the spray gun of 4mm, and ablation time of about 120s.
[0048] Example 1
[0049] The density is selected as 1.38 g / cm 3 , the C / C composite body with an opening rate of 26.3% was cut into cylindrical specimens with a diameter of 20 mm and a height of 8 mm;
[0050] Si powder and Zr powder with a particle size of 75 μm and a purity of 99.9% were selected, and a total of 100 g was weighed according to the molar ratio of Zr:Si=1:9. After mixing, they were named Zr1Si9. After the powder was uniformly embedded in the C / C composite body, the electrodes of the Joule heating device were connected, and the furnace was evacuated to vacuum.
[0051] The program of the Joule heating equipment is as follows: heating rate 1000℃ / s, holding temperature 1600℃, and holding for 60 min after reaching 1600℃; the cooling rate is set to 500℃ / min.
[0052] The total time used for preparing the C / C-SiC-ZrC composite material in this example is about 65 min.
[0053] Performance Testing:
[0054] The density of the C / C-SiC-ZrC composite material prepared in Example 1 ranges from 1.38 g / cm 3 Increased to 2.78 g / cm 3 , the opening rate dropped from 26.3% to 13.5%.
[0055] Figure 1 This is the macroscopic morphology of the C / C-SiC-ZrC composite material. It can be seen that the surface of the composite material is relatively flat and there is no residual metal. Figure 2 a is the XRD spectrum of the cross section of the C / C-SiC-ZrC composite material. It can be seen from the figure that the C / C-SiC-ZrC composite material prepared by this method is composed of only SiC, ZrC and a small amount of C, and there is no residual alloy or single substance.
[0056] Figure 2b is an SEM image of the cross section of the C / C-SiC-ZrC composite material. It can be seen from the figure that the white is ZrC ceramic, the dark gray is SiC ceramic, and the SiC surrounds the black pyrolytic carbon layer with a relatively clear interface, indicating that the C / C-SiC-ZrC composite material prepared by the present invention has no signs of corrosion of the carbon fiber.
[0057] The C / C-SiC-ZrC composite material prepared in Example 1 had a linear ablation rate of 2.975 μm / s and a mass ablation rate of 2.798 mg / s after 120 s of plasma ablation. Figure 3 This is the macroscopic morphology of the surface after ablation. It can be seen that the ablated surface is relatively flat without obvious ablation pits. Figure 4 a is the temperature curve of the composite material ablation process, and the ablation temperature is stable at 2100℃. Figure 4 As shown in b, only ZrO2 and a small amount of SiC exist. Compared with the C / C-SiC-ZrC composite material prepared in a conventional tube furnace in Comparative Example 1, the ablation resistance is significantly improved.
[0058] Example 2
[0059] The density is 1.40 g / cm 3 , the C / C composite body with an opening rate of 25.9% was cut into cylindrical specimens with a diameter of 20 mm and a height of 8 mm;
[0060] Si powder and Zr powder with a particle size of 75 μm and a purity of 99.9% were selected, and a total of 100 g was weighed according to the molar ratio of Zr:Si=9:1. After mixing, they were named Zr9Si1. After the powder was uniformly embedded in the C / C composite body, the electrode of the Joule heating device was connected, and the furnace was evacuated to vacuum.
[0061] The program of the Joule heating equipment is: heating rate 500℃ / s, holding temperature 1900℃, holding temperature for 55 min after reaching 1900℃; the cooling rate is set to 500℃ / min.
[0062] The total time used for preparing the C / C-ZrC-SiC composite material in this example is about 60 min.
[0063] Performance Testing:
[0064] The density of the C / C-ZrC-SiC composite material prepared in Example 2 ranges from 1.40 g / cm 3 Increased to 2.92 g / cm 3 , the opening rate dropped from 25.9% to 9.5%.
[0065] Figure 53 is an XRD spectrum of a cross section of a C / C-SiC-ZrC composite material. It can be seen from the figure that the C / C-ZrC-SiC composite material blank prepared by the present invention is mainly composed of ZrC and SiC ceramics, and no residual alloy or single substance exists.
[0066] Figure 6 This is the SEM image of the cross section of the C / C-SiC-ZrC composite material. It can be seen from the figure that the pores inside the material are basically filled with SiC and ZrC, the ceramic phase is not gathered on the surface, and there are no large pores inside the material.
[0067] After 120s of plasma ablation, the C / C-ZrC-SiC composite material prepared in Example 2 had a linear ablation rate of 3.547 μm / s, a mass ablation rate of 5.032 mg / s, and a complete ablation surface morphology without obvious ablation pits.
[0068] Example 3
[0069] The density is selected as 0.91 g / cm 3 , a C / C composite body with an opening rate of 50.2%; cutting it into cylindrical specimens with a diameter of 20 mm and a height of 8 mm;
[0070] Si powder and Zr powder with a particle size of less than 75 μm and a purity of 99.9% were selected, and a total of 100 g was weighed according to the molar ratio of Zr:Si=9:1. After mixing, they were named Zr9Si1. After the powder was uniformly embedded in the C / C composite body, the electrode of the Joule heating device was connected, and the furnace body was evacuated to vacuum.
[0071] The program of the Joule heating equipment is: heating rate 500℃ / s, holding temperature 1900℃, holding for 50 min after reaching 1900℃; the cooling rate is set to 1000℃ / min.
[0072] The total time used for preparing the C / C-ZrC-SiC composite material in this example is about 53 min.
[0073] Performance Testing:
[0074] The density of the C / C-ZrC-SiC composite material prepared in Example 3 is from 0.91 g / cm 3 Increased to 2.68 g / cm 3 , the opening rate dropped from 50.2% to 12.7%.
[0075] Figure 7 This is the XRD spectrum of the cross section of the C / C-ZrC-SiC composite material, which shows that the material is mainly composed of ZrC and SiC ceramics, without any residual alloy or single substance.
[0076] After 120s of plasma ablation, the C / C-ZrC-SiC composite material prepared in Example 3 had a linear ablation rate of 2.831 μm / s, a mass ablation rate of 4.185 mg / s, and a relatively complete ablation surface morphology without obvious ablation pits.
[0077] Example 4
[0078] The density is selected as 0.89 g / cm 3 , a C / C composite body with an opening rate of 49.6%; cutting it into cylindrical specimens with a diameter of 20 mm and a height of 8 mm;
[0079] Zr powder and Ti powder with a particle size of less than 75 μm and a purity of 99.9% were selected, and a total of 100 g was weighed according to a molar ratio of Zr:Ti=4:1. After mixing, they were named Zr4Ti1. After the powder was uniformly embedded in the C / C composite body, the electrodes of the Joule heating device were connected, and the furnace was evacuated to vacuum.
[0080] The program of the Joule heating equipment is: heating rate 500℃ / s, holding temperature 2000℃, and holding for 55 min after reaching 2000℃; the cooling rate is set to 500℃ / min.
[0081] The total time used for preparing the C / C-ZrC-TiC composite material in this example is about 60 min.
[0082] Performance Testing:
[0083] The density of the C / C-ZrC-TiC composite material prepared in Example 4 ranges from 0.89 g / cm 3 Increased to 2.57 g / cm 3 , the opening rate dropped from 49.6% to 13.2%.
[0084] Figure 8 This is the XRD spectrum of the cross section of the C / C-ZrC-TiC composite material, which shows that the material is mainly composed of ZrC and TiC ceramics, without any residual alloy or single substance.
[0085] After 120s of plasma ablation, the C / C-ZrC-TiC composite material prepared in Example 4 had a linear ablation rate of 4.125 μm / s, a mass ablation rate of 4.291 mg / s, and a relatively complete ablation surface morphology without obvious ablation pits.
[0086] Comparative Example 1
[0087] This comparative example was carried out in a similar manner to Example 1, except that the heating equipment in this comparative example was a tubular furnace, and the heating procedure was: heating to 1600°C at 10°C / min, keeping the temperature for 60 min, and cooling to room temperature with the furnace. The total time used in this comparative example was about 800 min.
[0088] Performance Testing:
[0089] The density of the C / C-SiC-ZrC composite material prepared in this comparative example was increased to 2.92 g / cm 3 , the opening rate dropped to 9.8%.
[0090] Fig. 9 This is a macroscopic morphology of the composite material prepared in this comparative example. Its surface is relatively flat, but it has many pores. Fig.10 This is the SEM spectrum of the cross-section of the composite material prepared in this comparative example. It can be seen from the figure that part of the SiC phase (gray) is in close contact with the carbon fiber (black), indicating that the ceramic phase seriously corrodes the carbon fiber. The reason is that the slower heating rate and longer holding time are conducive to the melting and infiltration of the powder, but the reaction with the carbon matrix is uncontrollable, causing the metal to corrode the carbon fiber.
[0091] After 120s of plasma ablation, the C / C-SiC-ZrC composite material prepared in Comparative Example 1 had a linear ablation rate of 4.138 μm / s and a mass ablation rate of 4.392 mg / s. Fig.11 As shown, there are obvious ablation pits in the ablation center area, and the oxide on the ablation surface falls off. Fig.12 a is the ablation surface temperature curve of the composite material. The ablation temperature is stable at 2100°C, which is similar to Example 1. Fig.12 b is the XRD pattern of the surface after ablation, which is mainly composed of ZrO2 and SiC, but the content of SiC is higher than that of Example 1, which may be related to the cracking or shedding of the oxide layer after ablation of the composite material to expose the matrix. The ablation performance of this comparative example is poor, mainly because the infiltration melt erodes the carbon fiber, reducing the ability of the composite material to resist plasma scouring during ablation, resulting in the shedding of the oxide layer and the reduction of ablation performance.
[0092] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a ceramic matrix composite material by rapid reaction infiltration, characterized in that: The method comprises: placing a C / C composite material blank embedded or covered by an infiltration raw material in a Joule heating device under vacuum or inert atmosphere, rapidly heating the blank by Joule heating and keeping the temperature for a certain period of time, so that the infiltration raw material and the C / C blank react and infiltrate rapidly, thereby obtaining a ceramic-based composite material, wherein the rapid heating rate is greater than or equal to 200°C / s.
2. The method for preparing ceramic matrix composite materials by rapid reaction infiltration according to claim 1, characterized in that: The C / C composite material blank contains carbon fiber and carbon matrix, and its density is 0.5-1.8 g / cm 3 , the opening rate is 1%~80%.
3. The method for preparing ceramic matrix composite materials by rapid reaction infiltration according to claim 2, characterized in that: The ceramic-based composite material consists of carbon fibers and a matrix, wherein the matrix consists of ceramics and unreacted carbon single substance.
4. The method for preparing ceramic matrix composite materials by rapid reaction infiltration according to claim 3, characterized in that: The ceramic is a ceramic formed by the reaction of the infiltration raw material and the carbon matrix or a ceramic brought in from the raw material during infiltration. The ceramic is a carbide or boride of metals and / or non-metals such as Si, Ti, Zr, Hf, Nb, Ta, rare earth, etc.
5. The method for preparing ceramic matrix composite materials by rapid reaction infiltration according to claim 4, characterized in that: The infiltration raw materials are metal or non-metallic elements, alloys such as Si, Ti, Zr, Hf, Nb, Ta, B, rare earth, and carbides, nitrides, borides, oxides of metal or non-metallic elements such as Si, Ti, Zr, Hf, Nb, Ta, rare earth, and mixtures or solid solutions of the above raw materials.
6. A method for preparing a ceramic matrix composite material by rapid reaction infiltration according to any one of claims 1 to 5, characterized in that: The infiltration raw material is in powder and / or block form. The particle size of the powder infiltration raw material is 10 nm-1 mm. The size of the block infiltration raw material is ≥ (1×1×1) mm. 3 .
7. A method for preparing a ceramic matrix composite material by rapid reaction infiltration according to any one of claims 1 to 5, characterized in that: The Joule heating device has a heating rate of up to 20,000°C / s, a maximum operating temperature of not less than 3,000°C, a maximum cooling rate of not less than 1,000°C / min, and a heat preservation time of not less than 15 minutes.
8. A method for preparing a ceramic matrix composite material by rapid reaction infiltration according to any one of claims 1 to 5, characterized in that: The conditions of the reactive infiltration are: heating to 1300°C~2100°C at a heating rate of 200~3000°C / s, keeping the temperature for 15~200min, and finally cooling to room temperature at a cooling rate of 100~1000°C / min.
9. A method for preparing a ceramic matrix composite material by rapid reaction infiltration according to any one of claims 1 to 5, characterized in that: The inert atmosphere is nitrogen and / or argon.
10. The method for preparing a ceramic matrix composite material by rapid reaction infiltration according to any one of claims 1 to 5, characterized in that: The obtained ceramic-based composite material can be applied to high-temperature structural parts, including at least one of a hypersonic aircraft nose cone, a wing leading edge, an engine nozzle, and a high-speed brake disc.
Citation Information
Cited By
Method for preparing ceramic-based composite material through ultra-fast infiltration and pyrolysis and application of ceramic-based composite material
CN121426582A
A method for preparing a carbon-based composite material, a carbon-based composite material and applications thereof
CN122809915A